Practical preparation of cyclopropenone 1,3-propanediol ketal - Mulks, Florian; Heckershoff, Robin; Zimmer, Marc; Hashmi, A. Stephen K. (Synthesis, 2020)
Cyclopropenone 1,3-propanediol ketal is an increasingly versatile building block for the introduction of various C3 and dioxaspiro units due to the emergence of numerous methodologies for the application of strained hydrocarbons. This Practical Synthetic Procedure gives an updated synthesis for a basic ketal of cyclopropenone with lowered solvent toxicity and a detailed step-by-step guide for the safe production of potassium amide in liquid ammonia and for its application in the synthesis of the cyclopropene ring.